Peran Mahasiswa Kukerta Dalam Bidang Pertanian Sebagai Wujud Pengabdian Di Desa Tanjung Berulak - Dhiva Raysha Ananda; Halim Hidayat; Izzati Hulwani; Kesya Zahra Muthia; Nur Afni Pratiwi; Ragil Azhari; Rafael Dwi Putra; Sovfi Yani; Syahrani Maryam (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
The purpose of this writing aims to help increase the knowledge of farmers to grow crops with hydroponic media to the community in Tanjung Berulak Village. The method used in this research is qualitative method. By processing data in the form of direct field observations and interviews with the community in Tanjung Berulak Village. The results obtained from the Kukerta student service in Tanjung Berulak Village show that the implementation of hydroponic media for the community can be implemented properly. And the community can also apply hydroponic media in farming in their environment.